Nanotechnology and energy : science, promises and limits - Lambauer, Jochen; Fahl, Ulrich, 1959-; Voss, Alfred (Singapore : Pan Stanford, 2013)
'This book gives an overview of nanotechnological applications within the value chain of the energy sector and evaluates selected applications and their direct and indirect impacts on the energy sector. It presents selected nanotechnological applications that influence the energy economy significantly. Furthermore, the authors give a comprehensive description of the impacts and outcomes of selected nanotechnological applications on energy consumption, energy sources, energy supply, and the energy industry in Germany and show the potential of these applications for energy savings, improvement in energy efficiency, and the reduction of emissions until 2030.'--Publisher.
Notes on the Contributors -- Foreword -- 1. Challenges in the Energy Sector and Future Role of Nanotechnology / Jochen Lambauer, Dr. Ulrich Fahl, Prof. Dr. Alfred Voβ -- 1.1. The Energy Sector in Germany and Its Future, Challenges -- 1.1.1. Demographic and Economic Development -- 1.1.2. Development of Prices for Fossil Energy Sources -- 1.1.3. Primary Energy Consumption -- 1.1.4. Electricity Generation -- 1.1.5. Final Energy Consumption -- 1.1.6. Energy Productivity and Energy Intensity -- 1.1.7. Emissions -- 1.2. Nanotechnology and Energy -- 2. Principles of Nanotechnology -- 2.1. Definition and Classification / Jochen Lambauer, Dr. Ulrich Fahl, Prof. Dr. Alfred Voβ -- 2.2. Scientific and Technical Background / Jochen Lambauer, Dr. Ulrich Fahl, Prof. Dr. Alfred Voβ -- 2.2.1. Nanomaterials -- 2.2.1.1. Point-shaped structures -- 2.2.1.2. Line-shaped structures -- 2.2.1.3. Layer structures -- 2.2.1.4. Pore structures -- 2.2.1.5. Complex structures -- 2.2.2. Top-Down and Bottom-Up Strategy -- 2.2.3. Tools and Production Processes -- 2.2.3.1. Vapour deposition -- 2.2.3.2. Manufacturing from liquid or dissolved raw materials -- 2.2.3.3. Manufacturing from solid raw materials -- 2.2.3.4. Lithography -- 2.2.3.5. Self-organisation -- 2.2.3.6. Nanoanalytics -- 2.3. Innovation and Economic Potential / Dr. Wolfgang Luther -- 2.3.1. Nanotechnology as a Cross-Cutting Innovation Field -- 2.3.2. Economic Relevance of Nanotechnology -- 2.3.3. Nanotechnology Companies in the Value-Added Chain -- 2.4. Risk and Safety Issues / Niels Boeing -- 2.4.1. The Image of Nanotechnology: Three Phases -- 2.4.1.1. Pre-2000: the futuristic phase -- 2.4.1.2. 2000-2006: the nanomarkets phase -- 2.4.1.3. Since 2006: the sceptical phase -- 2.4.2. A Systematic Approach to Nanotechnology Risks -- 2.4.2.1. Primary nanorisks: impacts on health and the environment -- 2.4.2.2. Secondary nanorisks: impacts on society and the economy -- 2.4.3. Conclusion -- 2.5. Public Perception of Nanotechnologies: Challenges and Recommendations for Communication Strategies and Dialogue Concepts / Dr. Antje Grobe, Nico Kreinberger -- 2.5.1. Introduction -- 2.5.2. Psychological, Social, and Cultural Factors of Risk Perception -- 2.5.3. Public Perception of Nanotechnologies: an International Comparison -- 2.5.4. Consumer's Perception of Nanotechnologies in German Language Areas -- 2.5.5. Attitudes Towards Nanotechnologies in the Energy Sector -- 2.5.6. Requirements for Consumer Communication -- 2.5.7. Conclusions: Recommendations for Communication Strategies and Dialogue Concepts -- 3. Examples for Nanotechnological Applications in the Energy Sector -- 3.1. Aerogels: Porous Sol-Gel-Derived Solids for Applications in Energy Technologies / Dr. Gudrun Reichenauer -- 3.1.1. Aerogels-Synthesis and Properties -- 3.1.1.1. Synthesis -- 3.1.1.2. Structural properties -- 3.1.2. Properties Meeting Applications -- 3.1.2.1. Thermal insulation -- 3.1.2.2. Components for energy storage -- 3.1.2.3. Catalysts supports -- 3.1.2.4. Other energy-related fields of application -- 3.1.3. Problems to be Solved for a Broad Introduction of Aerogels in Energy-Related Applications -- 3.1.4. Conclusions -- 3.2. Energy Sources and Conversion -- 3.2.1. Dye Solar Cells / Dr. Claus Lang-Koetz, Dr. Andreas Hinsch, Dr. Severin Beucker -- 3.2.1.1. DSC technology and its application -- 3.2.1.2. Characteristics of DSC modules -- 3.2.1.3. Manufacturing steps for DSC modules -- 3.2.1.4. Industrial production for DSC modules -- 3.2.1.5. Application scenarios for future DSC products -- 3.2.1.6. Environmental impact -- 3.2.1.7. Conclusions and outlook -- 3.2.2. Nanoscale Thermoelectrics -- a Concept for Higher Energy Efficiency? / Dr. Harald Btner, Jan Kig -- 3.2.2.1. Introduction -- 3.2.2.2. Initial concepts of nanoscale thermoelectrics -- 3.2.2.3. Current concepts of nanoscale thermoelectrics -- 3.2.2.4. Nanocomposite bulk materials -- 3.2.2.5. Summary and outlook -- 3.2.3. Nanostructured Ceramic Membranes for Carbon Capture and Storage / Dr. Martin Bram, Dr. Tim van Gestel, Dr. Wilhelm Albert Meulenberg, Prof. Dr. Detlev Ster -- 3.2.3.1. Requirements of membranes for gas separation in post- and pre-combustion power plants -- 3.2.3.2. Gas separation with microporous ceramic membranes -- 3.2.3.3. Membrane materials -- 3.2.3.4. Performance of microporous ceramic membranes -- 3.2.3.5. Summary and conclusion -- 3.3. Energy Storage and Distribution -- 3.3.1. Materials for Energy Storage / Dr. Wiebke Lohstroh -- 3.3.1.1. Materials for hydrogen storage -- 3.3.1.2. Physiorption materials -- 3.3.1.3. Chemisorption materials -- 3.3.1.4. Materials for energy storage in batteries -- 3.3.1.5. 'New' battery materials -- 3.3.1.6. Conclusions -- 3.4. Energy Use -- 3.4.1. Nanotechnology in Construction / Dr. Wenzhong Zhu -- 3.4.1.1. General development -- 3.4.1.2. Application areas -- 3.4.1.3. Future prospect -- 3.4.2. Active Windows for Daylight-Guiding Applications / Andreas Jel, Qingdang Li, Jg Clobes, Volker Viereck, Prof. Dr. Hartmut Hillmer -- 3.4.2.1. Introduction and basics -- 3.4.2.2. Complete active window -- 3.4.2.3. Regulation concepts for active windows -- 3.4.2.4. Production of micromirror arrays -- 3.4.3. Energy Efficiency Potential of Nanotechnology in Production Processes / Dr. Karl-Heinz Haas -- 3.4.3.1. Introduction -- 3.4.3.2. Types and properties of nanoscaled materials -- 3.4.3.3. Production processes of nanomaterials -- 3.4.3.4. Nanotechnologies in production processes -- 3.4.3.5. The vision of molecular manufacturing -- 3.4.3.6. Conclusion, summary, and outlook -- 4. Potential Analysis and Assessment of the Impact of Nanotechnology on the Energy Sector Until 2030 -- 4.1. Methodological Approach / Jochen Lambauer, Dr. Ulrich Fahl, Prof. Dr. Alfred Voβ -- 4.2. Environmental Impact and Energy Demand of Nanotechnology / Michael Steinfeldt -- 4.2.1. Environmental Reliefs Potentials of Nanotechnology -- 4.2.2. Evaluation of Specific Application Contexts: Life Cycle Assessment -- 4.2.3. Evaluation of Specific Manufactured Nanoparticles -- 4.3. Potentials of Nanotechnology for Improvements in Energy Efficiency and Emission Reduction / Jochen Lambauer, Dr. Ulrich Fahl, Prof. Dr. Alfred Voβ -- 4.3.1. Energy Sources and Conversion -- 4.3.1.1. Solar heat and photovoltaics -- 4.3.1.2. Fuel cells -- 4.3.1.3. Fuel additives -- 4.3.1.4. Nanostructured membranes -- 4.3.1.5. Thermoelectric generators -- 4.3.2. Energy Storage and Distribution -- 4.3.3. Energy Use -- 4.3.3.1. LED and OLED in illumination -- 4.3.3.2. New display technologies -- 4.3.3.3. Ultra-high-performance concrete -- 4.3.3.4. Insulation with vacuum-insulation panels -- 4.3.3.5. Polycarbonates for automotive glazing -- 4.3.3.6. Nano-lacquers -- 4.3.3.7. Nanocatalysts -- 4.3.3.8. Nanoparticles in synthetic production -- 4.3.3.9. Nanpoarticles in tyre compounds -- 4.3.3.10. Nano-based coatings to reduce friction -- 4.3.4. Theoretical Potentials of Nanotechnology -- 4.4. Scenario and Sensitivity Analyses for Impacts of Nanotechnological Applications / Jochen Lambauer, Dr. Ulrich Fahl, Prof. Dr. Alfred Voβ -- 4.4.1. Energy Sources and Conversion -- 4.4.1.1. Solar heat and photovoltaics -- 4.4.1.2. Fuel cells -- 4.4.1.3. Fuel additives -- 4.4.1.4. Nano-based membranes for carbon capture and storage -- 4.4.1.5. Thermoelectric generators -- 4.4.2. Energy Storage and Distribution -- 4.4.3. Energy Use -- 4.4.3.1. LED and OLED in illumination -- 4.4.3.2. New display technologies -- 4.4.3.3. Ultra-high-performance concrete -- 4.4.3.4. Insulation with vacuum-insulation panels -- 4.4.3.5. Polycarbonates for automotive glazing -- 4.4.3.6. Nano-lacquers -- 4.4.3.7. Nanocatalysts for styrene manufacturing -- 4.4.3.8. Nanoparticles in synthetic production -- 4.4.3.9. Nanoparticles in tyre compounds -- 4.4.3.10. Nano-based coatings to reduce friction -- 4.5. Comprehensive Subsumption of Nanotechnology in the Energy Sector / Jochen Lambauer, Dr. Ulrich Fahl, Prof. Dr. Alfred Voβ -- Index.
Includes bibliographical references and index.
Keywords: Power resources -- Technological innovations; Nanotechnology